Faktor-Faktor yang Mempengaruhi Pemilihan Lokasi Perumahan di Kota Banda Aceh - Harlini Putri; Abd. Jamal (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2014)
The objective of this study is to analyse factors that determine people’s decision on selection of housing location in or outside a complex. The study carried out in Banda Aceh used a logistic regression model. The results of the study showed that the independent variables, comfortability and buying price, were statiscally significant factors on community’s decision on housing selection. This might happen as people expect that the price of housing will increase in the future. Meanwhile, income and transportation cost were statistically not significant factors in housing selection. Based on the results, Banda Aceh Munipacility should participate in developing more comfortable compplex by providing security posts with personnels and by faciliting people to get easy access to home loan mortgage.